Analisis Pengaruh Model Flipped Classroom Berbantuan Peta Konsep terhadap Hasil Belajar IPAS Siswa Kelas V SD Negeri 2 Dangin Puri, Denpasar - Wulandari, Gusti Ayu Sri; Yasa, I Made Wiguna; Wijaya, I Komang Wisnu Budi (Alma Ata University Press, 2025)
Thelearningmodel isoneofthesupportingfactorsoflearningquality,initsapplicationitis important to choose the right model with learning needs. This study aims to determine the significant effect of the Flipped Classroom learning model assisted by concept maps on the learningoutcomes of students in scienceingradeVof SDNegeri 2 Dangin Puri, North Denpasar. This study is a quantitative study, namely experimental research with a quasi-experimental design (Quasi-ExperimentalDesign)usingadesign,namelynon-equivalentcontrolgroupdesign.The populationofthisstudywas56studentsingradeVofSDNegeri2DanginPuri,Denpasar.The samplewastakenusinga saturatedsamplingtechniquewherethe entirepopulationwasused as asample,namely28studentsinclassVAastheExperimentalclassandVBasthecontrolclass totaling 28 students. The data collection method uses a test with a multiple-choice test instrument. The research data were analyzed using inferential statistical techniques (t-test) independent sampletest..Theresultsoftheindependentsamplet-testanalysisonthelearningoutcomesofthe experimental group and the control group, the significance value obtained was 0.001 by comparingthesignificancelevelof0.05,thentheresultsofthet-testwithasignificanceof0.001 < 0.05. Descriptively, the average post-test score of the experimental class was 86.79 and was greater than the control class which only had a score of 67.68. ItcanbeconcludedthatHοisrejectedandHaisacceptedwhichstatesthatthereisan influenceof sciencelearningoutcomesbetweenthe groupgiventheFlipped Classroomlearning model treatment and the group using the lecture or conventional learning model on class V studentsofSDNegeri 2DanginPuri Denpasar inthe2024/2025AcademicYear.